Peran Work Life Balance dalam Memoderasi Hubungan Antara Konflik Pekerjaan dan Keluarga Terhadap Stres Pekerjaan - Husain Nurisman; M. Romli (Peneliti.net, 2022)
Work family conflict occurs when work roles (work to family conflict) and family roles (family to work conflict) do not support each other, causing conflict in the family or at work. Conflicts that occur between these roles can cause stress. One of them is job stress, which arises due to pressure at work that is not following workers' ability. This study was conducted to determine the effect of work to family conflict and family to work conflict on job stress and the effect of work-life balance on reducing or increasing work stress levels. This study also compares the effect of married or unmarried status. The results of this study are that work to family conflict and family work conflict can affect job stress even though work-life balance cannot be a moderating factor in both relationships. Both married and unmarried have the same effect on job stress caused by conflict. Exist both in the family and at work.